(untitled) (Fiep Bulletin - online, 2011)
This research has the objective of scoring points on international cooperation among students from different countries at the university and verifies the social status of foreign university students on access to health services and quality of life. It’s about an exploratory study that seeks to analyze the phenomenon of migration in diverse aspects, pointing out the psycho-socio-cultural aspects from social representations of access to health services and being an immigrant, emphasizing knowledge, images, attitudes and widespread beliefs collectively in the daily broadcast carried out with 51 foreign students in the Campus I of the Federal University of Paraíba, João Pessoa-PB, of both sexes and different countries. To collect data we used a multimethod approach with a consultation on secondary data from a semi-structured interview and the test of free association of words, with the stimulus inductors: access to health services and being an immigrant, previously scheduled, lasting average of thirty minutes for each participant. The data obtained from interviews were analyzed using the technique of thematic content analysis. Then, the interviews were submitted to the software Alceste, constituting a body composed of thirty interviews. The data seized from Alceste pointed to five great categories subsidized interpreted in the theory of social representations.